2022
DOI: 10.3389/fimmu.2022.996103
|View full text |Cite
|
Sign up to set email alerts
|

Joint together: The etiology and pathogenesis of ankylosing spondylitis

Abstract: Spondyloarthritis (SpA) refers to a group of diseases with inflammation in joints and spines. In this family, ankylosing spondylitis (AS) is a rare but classic form that mainly involves the spine and sacroiliac joint, leading to the loss of flexibility and fusion of the spine. Compared to other diseases in SpA, AS has a very distinct hereditary disposition and pattern of involvement, and several hypotheses about its etiopathogenesis have been proposed. In spite of significant advances made in Th17 dynamics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 241 publications
0
15
0
Order By: Relevance
“…Although the etiology and pathogenesis of AS have not been fully clarified, some studies have identified that the symptomatic feature described as the “bamboo‐like spine” is a characteristic of the classical autoimmune disorder AS, which typically begins with an inflammation in the sacroiliac joint. This disorder is a member of the SpA family of maladies, which cause inflammation to flare up in the spine, limb joints, ligaments, and tendons 111 . Although the pathogenic mechanism of AS is, as yet, undetermined, multiple theories on the triggering process have been put forward.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the etiology and pathogenesis of AS have not been fully clarified, some studies have identified that the symptomatic feature described as the “bamboo‐like spine” is a characteristic of the classical autoimmune disorder AS, which typically begins with an inflammation in the sacroiliac joint. This disorder is a member of the SpA family of maladies, which cause inflammation to flare up in the spine, limb joints, ligaments, and tendons 111 . Although the pathogenic mechanism of AS is, as yet, undetermined, multiple theories on the triggering process have been put forward.…”
Section: Discussionmentioning
confidence: 99%
“…Endoplasmic reticulum stress, which triggers the unfolded protein response and induces necrotic death and cytokine production, could be generated by an error‐prone folding process of certain HLA‐B27 alleles. Via the intrinsic HLA monitoring receptor, surface‐expressed HLA‐B27 molecules with an unusual shape could encourage the immune system to react in an improper way 111 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The term spondyloarthritis covers a heterogeneous set of conditions that can involve a variety of tissue ( Sharip and Kunz, 2020 ) including joints and the spine, specifically the sacroiliac joints ( Brown et al, 2020 ; Xiong et al, 2022 ). These inflammatory immune-mediated conditions can affect spinal tissues especially support tissues such as ligaments and their entheses of the axial skeleton ( Alber et al, 2022 ; Li et al, 2022 ).…”
Section: Influence Of Sex On Msk Tissues As An Adultmentioning
confidence: 99%